STUDY THE SUPPORTING GUIDELINE OF BIOLOGICAL GAS PRODUCTION FOLLOW IN SUFFICIENCY ECONOMY PHILOSOPHY, CASE STUDY : BIOLOGICAL GAS GROUP IN JARAGO VILLAGE AT MOO 6, MANANGDALUM, SAIBURI, PATTANI - มะกิเยาะ, นูรไอนี; เดโชชัย, อุดมศักดิ์; ดำรงวัฒนะ, จิตติมา; แขน้ำแก้ว, เดโช (Journal of MCU Nakhondhat, 2015)
The objective of this research were to study the supporting guideline of biological gas production follow in sufficiency economy philosophy, Case study : Biological Gas Group in Jarago village at Moo 6, Manangdalum, Saiburi, Pattani. The method of this research were fieldwork, analyze, synthesize and descriptive statistics result. This research was qualitative research. The research results found that: Biological gas production follow in sufficiency economy philosophy as follow; 1) equipment; they could buy them easily from market and good quality to use for a long time, 2) making the tank for ferment gas; they used the cement pipes that could produce in community, 3) making the tank for keep gas; they used the tank size 160 litres , and 4) they preserved the dunk and food scraps that kept from community and preserved them on 20 – 25 days so give to biological gas to gas tank always. The supporting guideline of biological gas production follow in sufficiency economy philosophy as follow; 1) to campaign to school, mosque, and community for realizing the salvage from dunk and food scraps, 2) could be the compost that replaced the chemical fertilizer, 3) biological gas was good friend with environment. The summarize results was biological gas production in Jarago village had reduced bad smell problem, water pollution, waste problem in community and could find waste which remnant from biological gas production would be organic fertilizer and brought about to make the career in community.